Penerapan Strategi Diferensiasi Konten dan Proses Pada Gaya Belajar Berbasis Model Problem Based Learning - Atikah, Isma; Fauzi, Muhammad Ali Rif’an; Firmansyah, Ridlo (Indonesian Journal Publisher, 2024)
Education is one of the dynamic manifestations of human culture and a prerequisite for development. Education plays a crucial role in creating high-quality and potential individuals as it is the primary means to enhance human resources. A teacher should take a step towards change, such as transforming traditional teaching techniques (lectures) that are teacher-centered into a more creative and innovative approach. One way for teachers to meet the needs of students is by considering diverse learning styles through differentiated learning. The purpose of this study is to describe the implementation of differentiated content and process learning strategies based on the Problem Based Learning model for various learning styles. The method used is qualitative descriptive with data collection strategies through direct observation. The research was conducted at Grujugan High School with the research subjects being all students of class X.1. Through the application of differentiated learning and the Problem Based Learning model, it is expected that teachers can tailor their teaching to the needs of students, thus creating student-centered learning. The results of this study indicate that the implementation of differentiated content and process learning strategies in class X.1 has been successful. Differentiated learning provides an opportunity for students to learn naturally and efficiently with teachers who can collaborate with the methods and approaches needed by students. There was an increase in student activity in learning before the teacher implemented differentiated learning and used the Problem Based Learning model. By understanding the implementation of differentiated learning, it is expected that teachers can tailor their teaching to the needs of students, thereby creating student-centered learning.